Investigations on dielectric resonators for applications below 1 GHz - VALENTIN, M.; ELCHEIKH, R. E. (Archives of Acoustics, 1991)
This paper is concerned with the design and analysis of UHF dielectric resonators operating below 1GHz in certain applications where quartz-based acoustic resonators of modest performance or metallic cavities are customary employed. Lowest-order modes of circular and rectangular dielectric resonator are considered. Mode identification is obtained with a network analyzer and from visual observation of microwave energy detected by liquid crystal plates. Design and performance of filter, discriminator and oscillator using partly metallized λ/4 dielectric resonators are presented.